Evaluation of an implementation project: The exercise physiology in aged care program. Issue 6 (17th April 2020) - Parfitt, Gaynor; Post, Dannielle; Penington, Alison; Davison, Kade; Corlis, Megan
Abstract : Aim: It is important for older adults to maintain the ability to be physically active, and to experience the benefits that physical activity brings. This study evaluates a 12‐week Accredited Exercise Physiologist‐led exercise program for vulnerable older adults living with dementia, delivered in a residential aged care facility in South Australia. The value of the program was also evaluated from the perspective of partners‐in‐care (family members and care staff). Methods: Participants (n = 59) were randomized to either an intervention or control group, based on their functional and cognitive status. Physical function, cognitive function and habitual physical activity were assessed at baseline and post‐intervention. In total, 51 family members and 44 care staff completed surveys or participated to understand their perspectives of residents' capacity to exercise, as well as their perceptions of the impact of the program. Results: Repeated measures ANOVA identified evidence for maintenance of physical function (timed‐up‐and‐go [ɳ 2 = 0.19], handgrip strength [ɳ 2 = 0.13]); however, there were no differences for objectively measured habitual activity or cognitive function. Evidence for a dose effect was demonstrated for the 2‐min walk and timed‐up‐and‐go associated with the number of individual sessions attended by a participant. Partners‐in‐care perceived greater improvement compared with deterioration across all measured factors [( P  < 0.01, partial eta 2 (ɳ 2 ) =0.19] ranged from 0.35 to 0.78) post‐intervention. Perceptions and expectations of who could benefit from participation were changed ( P  < 0.05) and indicated that all but the most severely declined residents would be likely to benefit. Conclusions: Data supporting the maintenance for some physical functions suggest that this type of program should be considered for older adults living with dementia in residential aged care facilities. Geriatr Gerontol Int 2020; : – .